2017
DOI: 10.1016/s0140-6736(17)31371-5
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in adolescents: a severe phenotype posing major clinical challenges and public health burden

Abstract: Type 2 diabetes in adolescence manifests as a severe progressive form of diabetes that frequently presents with complications, responds poorly to treatment, and results in rapid progression of microvascular and macrovascular complications. Although overall still a rare disease, adolescent type 2 diabetes now poses major challenges to paediatric and adult diabetes services in many countries. Therapeutic options are heavily curtailed by a dearth of knowledge about the condition, with low numbers of participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 79 publications
2
117
1
Order By: Relevance
“…The prevalence of T2DM varies broadly around the world, but most data relate only to the United States and some European countries . This study was the first school‐based report in Latin America to estimate the prevalence of T2DM and prediabetes among youth.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The prevalence of T2DM varies broadly around the world, but most data relate only to the United States and some European countries . This study was the first school‐based report in Latin America to estimate the prevalence of T2DM and prediabetes among youth.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, in Europe, T2DM is considered a rare disease, accounting for only 2% of new diabetes cases among youth . Although it is known that the number of obese children and adolescents is increasing worldwide, only limited data are available regarding T2DM outside Europe and the United States . In Brazil, a national survey recently showed that 8.4% of Brazilian adolescents were obese, and over 20% of those had metabolic syndrome, but prior to our study, no data were available on T2DM prevalence in this population.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Global reports also suggest that the pathophysiology, phenotype, treatment response and prognosis of youth onset diabetes differ significantly from later onset diabetes . This contributes to greater concern regarding the future health of young people, as youth onset diabetes (defined as that diagnosed before the age of 25 years) appears to progress more rapidly, be more difficult to treat, have more comorbidities, and have a higher risk of complications.…”
mentioning
confidence: 99%
“…There is also a greater risk of mental health concerns, and the diagnosis of diabetes appears to worsen any pre‐existing comorbidities, which is of great concern in an already very vulnerable population. Type 2 diabetes is known to carry a burden of stigma, potentially further isolating young people, and there has been a lack of research focusing on strengths or resilience factors that would enhance engagement and self‐management …”
mentioning
confidence: 99%